The effectiveness of multimedia learning: A study on student learning - Akbar Agisni; Dewi Novari; Gelasa Leander; Bintang Unggul Prawirawan; Amir Hamzah Pohan (Priviet Social Sciences Journal, 2023)
The use of multimedia in the learning process has become an increasingly popular trend in the field of education. This research aims to explore the effectiveness of multimedia learning and its impact on student achievement. In this study, multimedia is defined as the use of a combination of elements such as text, images, audio, video, and animation in learning. The methods used in this research include literature review and analysis of relevant studies. The findings from the literature review indicate that the use of multimedia in learning offers several advantages. Firstly, multimedia can enhance visual appeal and support diverse learning styles. Secondly, multimedia can improve information retention by providing interactive and memorable learning experiences. Thirdly, multimedia can enhance understanding of complex concepts through the use of concrete examples and visualizations. However, the effectiveness of multimedia learning is influenced by various factors. One key factor is the design of the multimedia itself. Good design should consider student characteristics, learning objectives, and the content to be delivered. Furthermore, the availability of adequate technological infrastructure is also necessary to support the use of multimedia in learning.